2005
DOI: 10.1093/cercor/bhj014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cortical Network Activity on Short-term Synaptic Depression

Abstract: Repetitive stimulation of synaptic connections in the cerebral cortex often induces short-term synaptic depression (STD), a property directly related to the probability of transmitter release and critical for the computational properties of the network. In order to explore how spontaneous activity in the network affects this property, we first studied STD in cortical slices that were either silent or that displayed spontaneous rhythmic slow oscillations resembling those recorded during slow wave sleep in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 48 publications
12
65
0
Order By: Relevance
“…Moreover, they found that this depression saturated rapidly and that increases in thalamic activity beyond background levels generated only a mild increased depression. Our results are in general agreement with the finding of a chronic, rapidly saturating depression at the geniculocortical synapse (see also Reig et al, 2006). In contrast to previous work, however, our results are based on the analysis of single LGNd afferents, not summed activity of many electrically driven LGNd afferents.…”
Section: Sustainedsupporting
confidence: 93%
“…Moreover, they found that this depression saturated rapidly and that increases in thalamic activity beyond background levels generated only a mild increased depression. Our results are in general agreement with the finding of a chronic, rapidly saturating depression at the geniculocortical synapse (see also Reig et al, 2006). In contrast to previous work, however, our results are based on the analysis of single LGNd afferents, not summed activity of many electrically driven LGNd afferents.…”
Section: Sustainedsupporting
confidence: 93%
“…We address tonic depression as a final candidate. Most cells are silent in slices, but in vivo their spontaneous activity may induce tonic short-term synaptic depression (Boudreau and Ferster, 2005;Reig et al, 2006;Hermann et al, 2007;Wang et al, 2010). In slices, a fast recovery phase has been observed, which depends on calcium buildup within the endbulb (Wang and Manis, 2008;Yang and Xu-Friedman, 2008).…”
Section: Low Release Probability Of the Endbulb Of Held In Vivomentioning
confidence: 99%
“…Network responsiveness after the cessation of an Up state may be reduced through use-dependent depression of recurrent cortical connections (Crochet et al, 2004;Crochet and Petersen, 2006;Reig et al, 2006), the buildup of a slow afterhyperpolarization (Sanchez-Vives and McCormick, 2000;McCormick et al, 2003;Shu et al, 2003a), reduction in synaptic potentials through activity-dependent decreases in extracellular [Ca 2ϩ ] (Crochet and Petersen, 2006), or the slow activation or inactivation of a voltage-dependent inhibitory conductance (Bal and McCormick, 1996;Compte et al, 2003). The disproportionately increased excitability of fast-spiking inhibitory interneurons during the Up state may also result in reduced recurrent network activity, by enhancing the inhibitory contribution to whisker-evoked responses and consequently reducing the ability of excitatory inputs to initiate action potentials.…”
Section: Mechanisms Of Cyclical Changes In Responsivenessmentioning
confidence: 99%
“…Increased corticothalamic feedback during the Up state may also shift the thalamus out of the burst firing mode, resulting in a decrease in the number or frequency of spikes initiated in thalamocortical neurons by the whisker movement (McCormick and von Krosigk, 1992;Weyand et al, 2001) [see, however, Haslinger et al, (2006)]. Finally, tonic activity during the Up state may reduce responses to brief whisker stimuli through synaptic depression at the thalamocortical synapse (Gil et al, 1997;Beierlein and Connors, 2002;CastroAlamancos and Oldford, 2002;Hirata and Castro-Alamancos, 2006;Reig et al, 2006).…”
Section: Mechanisms Of Cyclical Changes In Responsivenessmentioning
confidence: 99%